PENGEMBANGAN DOSEN DI LINGKUNGAN SEKOLAH TINGGI ILMU SOSIAL DAN ILMU POLITIK AMAL ILMIAH YAPIS WAMENA KABUPATEN JAYAWIJAYA - Nur Aini (Master of Public Administration, Universitas Slamet Riyadi, 2016)
Implementation of development policies carried out by the facultyCollege of Social Sciences and Political Science Jayawijaya.Implementation of development policies carried out by the facultyCollege of Social Sciences and Political Science JayawijayaWamena is a strategic step in order to achieve quality lecturers. Thepurpose of this study was to analyze: how policy implementationlecturer in education programs formal and non-formal education, identifyand analyze the factors supporting and inhibiting factors in thedevelopment of lecturers, and efforts to improve the effectiveness of theimplementation of development policy lecturer at STISIP-AI YapisWamena. This research is a qualitative descriptive approach. The resultsshowed that there was a lack of clarity contents of the policy, the budgetprovided inadequate, dispositions related to cognition and organizationalstructures associated with coordination. Efforts to improve theeffectiveness of policy implementation by providing opportunities forfaculty to continue their education in order to achieve academicqualifications. Advice given on this research, lecturers developmentprogram in the STISIP A-I Yapis Wamena should be improved.Keywords : Implementation, Policy, Development Lecturer